2017
DOI: 10.1007/s00775-017-1457-0
|View full text |Cite
|
Sign up to set email alerts
|

Selenium speciation in the Fountain Creek Watershed and its effects on fish diversity

Abstract: Se is an environmental concern as it can be toxic if present in high concentrations even though it is a dietary requirement for all animals. Se levels are a special concern in the Fountain Creek Watershed located in southeastern Colorado whose geological source is the Se-rich Pierre Shale. Segments of Fountain Creek have Se water levels that exceed the current EPA limit of 5 µg/l. In the studies described here, the effects of river water containing selenium were examined on fish populations at different sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…While Se toxicity is linked to particular species [ 5 , 12 , 13 , 14 , 16 , 20 ] and the presence of selenite (SeO 3 2− ) [ 21 , 22 ], many environmental studies only measure and report the total amount of elemental Se. When analyzing and investigating Se speciation, a better understanding of the interaction of Se species in a natural environment is gained [ 5 , 7 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ]. Recent studies of fish in the Fountain Creek Watershed demonstrated that high numbers of fish species can be observed at sites with high levels of Se [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While Se toxicity is linked to particular species [ 5 , 12 , 13 , 14 , 16 , 20 ] and the presence of selenite (SeO 3 2− ) [ 21 , 22 ], many environmental studies only measure and report the total amount of elemental Se. When analyzing and investigating Se speciation, a better understanding of the interaction of Se species in a natural environment is gained [ 5 , 7 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ]. Recent studies of fish in the Fountain Creek Watershed demonstrated that high numbers of fish species can be observed at sites with high levels of Se [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing and investigating Se speciation, a better understanding of the interaction of Se species in a natural environment is gained [ 5 , 7 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ]. Recent studies of fish in the Fountain Creek Watershed demonstrated that high numbers of fish species can be observed at sites with high levels of Se [ 21 ]. This work led to the hypothesis that the toxicity is dependent on the presence of toxic Se species and not the total Se level [ 21 ] and support the need for additional studies that consider the effects of Se species on different types of fish.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations